PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL THINK PAIR SHARE BERBANTUAN MEDIA PaPI DI KELAS V SEKOLAH DASAR - Sulistiyani; Ika Ari Pratiwi; Erik Aditia Ismaya (STKIP Subang, 2023)
The purpose of this study was to describe the increase in student learning outcomes after the implementation of the Think Pair Share model assisted by PaPI media in social studies and civics learning in class V Theme 9 SD N 4 Rahtawu which can be used as reference material for teachers to improve the quality of the learning process in class. The type of research used is Classroom Action Research (CAR) with a quantitative and qualitative approach. The CAR model used in this study is the Kemmis and Mc Taggart model, with two cycles and two meetings of 2 x 35 each cycle. CAR steps taken are planning, implementing, observing, and reflecting. The data collection instruments used were tests, observations, interviews, and documentation. The results showed that the Think Pair Share (TPS) model assisted by PaPI media was proven to be able to improve student learning outcomes. Cycle I average percentage of learning outcomes obtained by 79.67%, and increased in cycle II by 82.57%. The percentage increase is 3.64% with very good criteria. It was concluded that learning using the Think Pair Share (TPS) learning model assisted by PaPI media can improve student learning outcomes.